Information System For The Handling Of Family Services Agency’s Records From The Popayán Municipality - Solano Benítez, Ingrid Paola; Garcés, Sara Donnelly; Arias, Kelly; Botero, Paola; Burbano, Julie (Ingeniería Solidaria, 2011)
This work shows the development of the so-called “Simexco” thesis project, an information system that allowed improving the processes of records’ handling and control within family services agency from Popayán municipality. It is structured in the following way: first, the family services agency from Popayán Municipality is described, then, the methodology carried out for the development of Simexco is explained; and finally, the results obtained are shown with their respective analysis.
Keywords: plaintiff; actor; format; records; information system